1988
DOI: 10.1139/v88-292
|View full text |Cite
|
Sign up to set email alerts
|

Main group (IIIA or 13) complexes of benzohydroxamic acid and the crystal structure of tris(benzohydroxamato)indium(III)

Abstract: Thispaper is dedicated to Professor Charles A. McDo\vell on the occasion of his 70th birthdayCAREY A. MATSUBA, STEVEN J. RETTIG, and CHRIS ORVIG. Can. J. Chem. 66, 1809Chem. 66, (1988. A series of tris(benzohydroxamato)metal(III) complexes has been prepared and characterized wherein the metals are aluminum, gallium, and indium. The complexes are synthesized in high yield from aqueous solution. The indium complex, as its ethanol solvate In(C7H6N02)3.C2H50H, has been studied by single crystal X-ray diffraction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

1991
1991
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 18 publications
2
4
0
Order By: Relevance
“…The robust formation of identical Ga/In-(hydroxamate) 3 nodes in these MOMs suggested that these moieties were stable and favored, concurring with previously reported hydroxamate-chelated Group 13 metal complexes. 37,38 Moreover, similar phenomena were recorded in the MOF literature where identical PBUs/SBUs could be interconnected by ligands of the same basic geometry to form diverse topologies. 39−42 For SUM-82, NH 3 •H 2 O was a key factor in the reaction between In(NO 3 ) 3 •4.5H 2 O and H 2 -TDHA when used as a modulator (Figure 3a).…”
Section: ■ Results and Discussionsupporting
confidence: 65%
“…The robust formation of identical Ga/In-(hydroxamate) 3 nodes in these MOMs suggested that these moieties were stable and favored, concurring with previously reported hydroxamate-chelated Group 13 metal complexes. 37,38 Moreover, similar phenomena were recorded in the MOF literature where identical PBUs/SBUs could be interconnected by ligands of the same basic geometry to form diverse topologies. 39−42 For SUM-82, NH 3 •H 2 O was a key factor in the reaction between In(NO 3 ) 3 •4.5H 2 O and H 2 -TDHA when used as a modulator (Figure 3a).…”
Section: ■ Results and Discussionsupporting
confidence: 65%
“…For the corresponding metalate [{Li(THF) 2 } 2 {Li(THF)}{In(( S )-BINOLate) 3 }]·[{Li(THF) 2 }{Li(THF)} 2 {In(( S )-BINOLate) 3 }] 2 · 8toluene a mean value of 2.15 Å was found . Quite similar In−O bond lengths of 2.13−2.15 Å were found in the complexes In(acac) 3 , In[ON(H)C(O)Ph] 3 ·EtOH, and In(1,2-O 2 C 7 H 5 ) 3 , all containing In centers with CN 6. A drastic elongation of the metal−oxygen distances occurred on changing to CN 8.…”
Section: Resultsmentioning
confidence: 73%
“…The particularly large difference in these complexes is most likely due to the special electronic features of the hydroxypyranone ligand, as the corresponding differences in hydroxypyridin-4-one or hydroxamate are much smaller: 0.03 Å in tris(3-hydroxy-4-pyridinone)indium 32 and 0.02 Å for tris(benzohydroxamato)indium. 33 Accordingly, a quite large difference of 0.055 Å, has been observed for tris-(maltol)aluminum, 34 although in this complex the coordination geometry is meridional.…”
Section: Resultsmentioning
confidence: 87%